Dear Edward - Napolitano, Ann (New York : The Dial Press, 2020)
A twelve-year-old boy struggles with the worst kind of fame--as the sole survivor of a notorious plane crash.
"Read with Jenna"-- Cover.
A novel.
Keywords: Airplane crash survival -- Fiction; Grief -- Fiction; Loss (Psychology) -- Fiction; Bildungsromans